Enzymatic Liquefaction and Characterization of Mangifera laurina Blume - Lejaniya Abdul Kalam Saleena; Kelly Yie Lin Tan; Lee Sin Chang; Liew Phing Pui (Техника и технология пищевых производств, 2024)
The fruit Mangifera laurina Blume lacks sufficient research attention, with no literature available on its physicochemical properties, proximate nutritional composition, carotenoid content, or enzyme liquefaction process. Therefore, we aimed to optimize the parameters for enzymatic liquefaction of M. laurina puree and comprehensively analyze its characteristics. Homogenized pulp of M. laurina was treated with different enzymes (Pectinex Ultra SPL, Celluclast, Fungamyl, and Termamyl). Pectinex Ultra SPL was selected as the most effective enzyme as it significantly decreased viscosity and increased juice yield. Pectinex Ultra SPL was then used to treat the homogenized pulp at different concentrations (0–4.0%), different incubation times (0–2.5 h), and different incubation temperatures (25–60°C). We considered these parameters as independent variables and studied their effects on viscosity, juice yield, total soluble solids, pH, and color to establish optimum conditions for the enzymatic liquefaction of M. laurina pulp. The recommended enzymatic liquefaction conditions were set as 2.0% Pectinex Ultra SPL at 45°C for 2.0 h. The optimized enzyme-liquefied mango puree showed a noteworthy decrease in total carotenoids (174.15 ± 0.04 µg/100 g), crude protein, crude fat, and crude fiber, compared to fresh mango puree. However, enzymatic liquefaction provided the mango puree with higher contents of moisture and ash, better water activity, and higher juice yield, compared to fresh mango puree. Enzymatic liquefaction of fruit juice provides advantages in terms of improved digestion, increased yield, and enhanced eco- nomic profit. Its ability to enhance nutrient availability, increase extraction rates, and optimize production processes makes it a valuable technique in various food industries.